(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To identify factors associated with cesarean section at Nghe An General Friendship Hospital during 2024-2025. Methods: An analytical cross-sectional study was conducted on 201 women who delivered at Nghe An General Friendship Hospital from June 1, 2024 to June 1, 2025. Associations between cesarean section and selected factors were assessed using Chi-square tests, with a significance level of p < 0,05. Results: The cesarean section rate was 41,8%. Factors significantly associated with cesarean section included maternal age ≥35 years (69,1% vs. 23,3%; p < 0,001), previous cesarean section (100% vs. 29,1%; p < 0,001), multiparity (49,5% vs. 33,3%; p = 0,022), non-cephalic fetal presentation (91,7% vs. 38,6%; p < 0,001), and conception via assisted reproductive technology (IVF) (90,0% vs. 39,3%; p = 0,002). No significant associations were found with residence, gestational age, history of miscarriage/stillbirth, or maternal comorbidities (p > 0,05). Conclusion: Cesarean section was associated with several maternal and pregnancy-related factors, particularly previous cesarean section, abnormal fetal presentation, and IVF conception. These findings may help guide more appropriate use of cesarean section in clinical practice.